NATURAL RESISTANCE Of MICROORGANISMS TO ANTIBIOTICS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article examines the importance of studying the natural resistance of microorganisms to antibiotics. Microorganisms have developed various mechanisms to protect themselves from antibiotics, which are related to their evolution, genetic changes, and natural selection processes. The natural resistance of microorganisms helps them survive during antibiotic treatment, which highlights the need to develop new treatment methods. A deep understanding of the natural resistance of microorganisms is crucial for ensuring the effective functioning of antibiotics and developing strategies to combat antimicrobial resistance.